Technology in Rehabilitation: Evaluating the Single Leg Squat Exercise with Wearable Inertial Measurement Units - Whelan, Darragh F.; O'Reilly, Martin A.; Ward, Tomás E.; Delahunt, Eamonn; Caulfield, Brian (Methods of Information in Medicine, 2017)
Background: The single leg squat (SLS) is a common lower limb rehabilitation exercise. It is also frequently used as an evaluative exercise to screen for an increased risk of lower limb injury. To date athlete/patient SLS technique has been assessed using expensive laboratory equipment or subjective clinical judgement; both of which are not without shortcomings. Inertial measurement units (IMUs) may offer a low cost solution for the objective evaluation of athlete/patient SLS technique.Objectives: The aims of this study were to determine if in combination or in isolation IMUs positioned on the lumbar spine, thigh and shank are capable of: (a) distinguishing between acceptable and aberrant SLS technique; (b) identifying specific deviations from acceptable SLS technique.Methods: Eighty-three healthy volunteers participated (60 males, 23 females, age: 24.68 +/− 4.91 years, height: 1.75 +/− 0.09 m, body mass: 76.01 +/− 13.29 kg). All participants performed 10 SLSs on their left leg. IMUs were positioned on participants’ lumbar spine, left shank and left thigh. These were utilized to record tri-axial accelerometer, gyroscope and magnetometer data during all repetitions of the SLS. SLS technique was labelled by a Chartered Physiotherapist using an evaluation framework. Features were extracted from the labelled sensor data. These features were used to train and evaluate a variety of random-forests classifiers that assessed SLS technique.Results: A three IMU system was moderately successful in detecting the overall quality of SLS performance (77% accuracy, 77% sensitivity and 78% specificity). A single IMU worn on the shank can complete the same analysis with 76% accuracy, 75% sensitivity and 76% specificity. Single sensors also produce competitive classification scores relative to multi-sensor systems in identifying specific deviations from acceptable SLS technique.Conclusions: A single IMU positioned on the shank can differentiate between acceptable and aberrant SLS technique with moderate levels of accuracy. It can also capably identify specific deviations from optimal SLS performance. IMUs may offer a low cost solution for the objective evaluation of SLS performance. Additionally, the classifiers described may provide useful input to an exercise biofeed-back application.
Keywords: Exercise therapy; biomedical technology; lower extremity; physical therapy speciality; inertial measurement units